Active control of micro-droplets by hybrid magnetically driven microtool - Presto, Yoko Yamanishi; Kihara, Yuki; Sakuma, Shinya; Arai, Fumihito (2009 IEEE/SICE International Symposium on System Integration, 2009)
We propose a hybrid polymer-metal magnetically driven microtool (MMT) featuring elasticity and rigidity. An electroplated magnetic metal axle is installed directly at the center of the MMT during molding. The result is a hybrid MMT whose fixed axes move elastically in a specific direction and whose center axle is rigid, preventing bending by unwanted external force. The axle' s higher magnetism contributes to powerful actuation. The hybrid MMT we designed provides on-demand droplet dispensation on chips. Its parallel plate is constrained translationally. Hybrid MMT displacement is 300 ¿m - 6 times greater than that of the conventional MMT. On-demand droplet generation produces a 177.7±2.3 ¿m droplet.